(untitled) (Al-Academy, 2024)
The research sheds light on the results of the influence of the artist’s self-consciousness on the nihilistic philosophy of interpreting the aesthetic experience, taking the sculptor Alberto Giacometti as a model. The research is divided into several chapters, where the first chapter was methodological in which I presented the research problem, which I concluded with the question: What is the importance of self-awareness in interpreting the aesthetic experience under the influence of Nihilistic philosophy? The importance of the research was summarized in investigating the impact of nihilistic philosophy and its impact on self-awareness to interpret the aesthetic experience. The aim of the research was to identify the impact of nihilistic philosophy on self-awareness to interpret the aesthetic experience. The limits of the research were in the objective limit, the influence of nihilistic philosophy in the aesthetic experience of the sculptor Albert Giacometti, the spatial limit: France, time limit: 1932-1961, and I defined the most important terms in the research, such as the terms subjectivism and nihilism. As for the second chapter, within the theoretical framework, I divided it into three sections. The first topic: a general vision about the concepts of subjectivism and nihilism, and the second topic: the aesthetic concepts of nihilistic philosophers. In it It dealt with the opinions of four nihilistic philosophers on art and beauty from a nihilistic vision (Nietzsche, Søren Kieckgaard, Heidegruppoul Sartre), and the third topic: the aesthetic experience and its nihilistic interpretation. Through studying the most important modernist artistic schools that were influenced by nihilistic philosophy and reviewing its results in the aesthetic experience, and in the third chapter within the procedural framework of the research, in which I dealt with the research methodology, the research community, the research tool, and the research sample in which I dealt with four works by the artist Alberto Giacometti, and then I analyzed the sample through The models chosen for analysis, as for the fourth chapter, in which the results were drawn, the most prominent of which was the artist in his artistic performance, is a searcher for the tangible and encoded aesthetic truth behind the phenomena and manifestations of the artistic work. Reducing and peeling the art form is to reveal its essence and reveal and reveal the truth of its existence. The artist’s imagination dives into the aesthetic form itself to weave a new form composed of the artist’s self with the apparent formation of external assets. Through reductionism, the artist generalized his nihilistic vision of the human formal achievement, simplification and simplification. Then List sources and references.